Odpowiedzi

2010-04-12T16:21:58+02:00
X+x-2 = 75% x +2*85% x - 1,7
x+x-2=0,75x+2*0,85x-1,7
x+x-0,75x-1,7x=-1,7+2
-0,5x=0,3
x=-0,6
2010-04-12T16:28:39+02:00
X+x-2=75%x+2*85%x-1,7
x+x-75%x-2*85%x=-7+2
2x-75%-2*85%=-7+2
1,25%x-1,70%x=-5
-0,35%x=-5/:(-35)
x=-4,65x


nie jestem pewny .

2010-04-12T16:37:34+02:00
X + x - 2 = 75% x + 2 * 85% x - 1,7
2 x - 2 = 0,75 x + 2 * 0,85 x - 1,7
2 x -2 = 2,45 x - 1,7 | + 1,7
2 x - 0,3 = 2,45 x | - 2 x
- 0,3 = 0,45 x | *5
- 1,5 = 2,25 x | : 0,25
- 6 = 9 x
- ⁶/₁ = ⁹/₁ x | : 9
- ⁶/₁ : 9 = x
- ¹/₆ * 9 = x
- ⁹/₆ = x
x = - 1 ¹/₂ = - 1,5